Pengembangan Instrumen Penilaian Unjuk Kerja dalam Kegiatan Praktikum pada Pokok Bahasan Fluida Dinamis Kelas XI SMA - Aswin Hermanus Mandolang; Jeane Cornelda Rende; Angriyarso Dilapanga (Program Studi Pendidikan Fisika Jurusan Fisika Fakultas Matematika, Ilmu Pengetahuan Alam, dan Kebumian (FMIPAK), Universitas Negeri Manado, 2022)
This research has been carried out to develop performance evaluation instruments on the subject of dynamic fluid physics subjects in class XI MIA III SMA Negeri 1 Bolaang which were developed. The method used in this research is research and development (research and development). The subjects in this study were students of class XI MIA III in the academic year 2019/2020, amounting to 35 people. The instrument used in collecting research data was divided into two, namely the validation format of the performance appraisal instrument to obtain valid data and the teacher's questionnaire response format to obtain effective data. Based on the validation data of the revised performance appraisal instrument 2 times, the performance appraisal instrument fulfills a valid category with an average score of 0.79, and the teacher response questionnaire fulfills a valid category with an average score of 0.80. This indicates that the performance appraisal instruments developed are perfect and feasible to use.